Advancements in Dermatological Applications of Curcumin: Clinical Efficacy and Mechanistic Insights in the Management of Skin Disorders - Mo Z; Yuan J; Guan X; Peng J (Dove Medical Press, 2024)
Zhiming Mo,1 Jiayi Yuan,1 Xuelian Guan,1 Jianhong Peng2 1Department of Pharmaceutical Center, Dongguan Traditional Chinese Medicine Hospital, Dongguan, 523000, People's Republic of China; 2Department of Internal Medicine, Dongguan Traditional Chinese Medicine Hospital, Dongguan, 523000, People's Republic of ChinaCorrespondence: Jianhong Peng, Department of Internal Medicine, Dongguan Traditional Chinese Medicine Hospital, No. 3, Dongcheng Section, Songshan Lake Avenue, Dongcheng District, Dongguan, Guangdong Province, 523000, People's Republic of China, Tel +86 0769-22245614, Email pengjhzyy@outlook.comAbstract: Curcumin, derived from Curcuma longa (turmeric), exhibits significant potential in dermatology, addressing conditions like atopic dermatitis, psoriasis, chronic wounds, skin cancer, and infections through its anti-inflammatory, antioxidant, anticancer, and antimicrobial properties. This review synthesizes evidence on curcumin's mechanisms, including modulation of immune responses and promotion of wound healing, showcasing its efficacy in reducing inflammation, cytokine levels, and enhancing skin barrier functions. Studies highlight curcumin's ability to selectively target tumor cells, suggesting a multifaceted approach to cancer therapy with minimal side effects. Despite promising therapeutic benefits, challenges remain in bioavailability, potency, and targeted delivery, underscoring the need for further research to optimize dosages, delivery methods, and assess long-term safety. The integration of curcumin into dermatological practice requires a balanced consideration of evidence-based efficacy and safety. Curcumin's comprehensive utility in dermatology, coupled with the necessity for advanced scientific exploration, emphasizes the importance of combining traditional knowledge with contemporary research to improve patient care in dermatology. This approach could significantly enhance outcomes for individuals with skin-related conditions, marking curcumin as a versatile and promising agent in the field.Keywords: curcumin, atopic dermatitis, psoriasis, chronic wounds, skin cancer